Assessing climate-growth relationships with daily and monthly observational and gridded meteorological data - Nina Škrk Dolar; Katarina Čufar; Jernej Jevšenak (Les)
We compared climate-growth relationships by correlating tree-ring variation with daily and monthly meteorological data obtained from the stations of the Slovenian Environment Agency (ARSO) and modelled data from the SLOCLIM database. Tree-ring width series for analyses were obtained from previously collected European beech (Fagus sylvatica) tree-ring data from 30 sites all over Slovenia. Climate-growth correlations were calculated to evaluate whether daily meteorological data exhibits stronger correlations than monthly data. We also compared the maximum correlation coefficients using meteorological station data and gridded SLOCLIM data. The analysis was conducted using the dendroTools R package, incorporating data on daily and monthly average air temperatures and precipitation sums from the period 1960–2018. Our findings revealed significantly higher maximum correlation coefficients for daily data compared to monthly data, underscoring the importance of using daily data, particularly for precipitation. However, no significant difference was observed between maximum correlation coefficients using the meteorological station and modelled data, and the difference did not change significantly with increasing altitude.